PENGARUH MODEL PEMBELAJARAN COOPERATIVE SCRIPT BERBANTUAN MEDIA PICTURE BALLOON RIDE TERHADAP KETERAMPILAN MEMBACA NYARING SISWA - Hesti Handayani; Anni Malihatul Hawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of cooperative script learning model assisted by picture balloon ride media on students reading aloud skills. The problem faced is the low reading aloud skills. This study uses a quantitative approach with a population of all second-grade students of SD N Bandungan 01, while the sample is students of class II A and II B SD N Bandungan 01. Data analysis was carried out through normality tests, homogeneity tests, independent sample t-tests and regression tests. The results of the study show: (1) There is a significant difference between the experimental class using cooperative script learning model assisted by picture balloon ride media and the control class using cooperative script model without picture balloon ride media, with a significance value of 0.001 < 0.05 based on the independent t-test. (2) There is an effect of cooperative script learning model assisted by picture balloon ride media on students reading aloud skills, with a significance value of 0.006 < 0.05 based on the regression test. The conclusion of this study is that the cooperative script learning model assisted by picture balloon ride media is effective in improving students reading aloud skills.